2021
DOI: 10.3390/polym13071028
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Form Transition and Crystallization Behavior of the Transparent Polyamide

Abstract: A transparent polyamide, poly(4,4′-aminocyclohexyl methylene dodecanedicarboxylamide) (PAPACM12), was studied and characterized by in situ wide-angle X-ray diffraction (WAXD) to establish the relationship between its crystallization behavior, crystalline form transition under external fields, and macroscopic properties. During the heating process, cold crystallization occurred and increased, and there was no form transition below the melting point. During the isothermal process, PAPACM12 exhibited the same cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The influence of different proportions of fillers (MoS 2 and PFA) on the mechanical properties of PA10T‐FM composites was evaluated through tensile, bending, and impact measurements 45 . The findings from the tensile testing are presented in Figure 10, and the mechanical performance parameters, including tensile strength, breaking elongation, bending strength, bending modulus, and Izod impact strength, are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of different proportions of fillers (MoS 2 and PFA) on the mechanical properties of PA10T‐FM composites was evaluated through tensile, bending, and impact measurements 45 . The findings from the tensile testing are presented in Figure 10, and the mechanical performance parameters, including tensile strength, breaking elongation, bending strength, bending modulus, and Izod impact strength, are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of different proportions of fillers (MoS 2 and PFA) on the mechanical properties of PA10T-FM composites was evaluated through tensile, bending, and impact measurements. 45 The findings from the tensile testing are presented in Figure 10, and the mechanical performance parameters, including tensile strength, breaking elongation, bending strength, bending modulus, and Izod impact strength, are summarized in Table 4. It can be observed that as the fillers content increased, the tensile strength and Izod impact strength of PA10T-FM composites exhibit a gradual improvement, while the breaking elongation shows a slight decrease.…”
Section: Mechanical Characteristics Of Pa10t and Pa10t-fm Compositesmentioning
confidence: 99%
“…These peaks can be associated respectively with the (100) and (010/110) lattices in the α-crystalline phase of PA1012. 32 It should be noted that all WAXD curves exhibit a sudden decline at 14.8 and 20.6 , respectively, where the signal intensity is zero. This unavoidable phenomenon is attributed to the multiple detectors assembling.…”
Section: Crystallization Behaviormentioning
confidence: 93%
“…To date, several approaches have been proposed for improving mechanical properties of polymers, such as blending with reinforcing fillers and regulating intrinsic crystal structures [16][17][18][19][20][21]. Among them, regulating intrinsic crystal structures of polymers is a great method for improving mechanical properties due to the low cost and regardless of interfacial compatibility between polymer and filler [16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%